2014
DOI: 10.1097/iae.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap Technique for Surgical Repair of Myopic Macular Holes

Abstract: Vitrectomy with the inverted internal limiting membrane flap technique may be an effective addition to surgical options for treating myopic macular holes. Spectral domain optical coherence tomography images confirm that the process of foveal architectural repair after this surgery continues over at least a 12-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
117
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 18 publications
6
117
1
6
Order By: Relevance
“…Kuriyama and Michalewska et al 21, 22 also found that the inverted ILM flap technique contributed to a high macular hole closure rate in highly myopic eyes. We therefore hypothesized that the inverted ILM flap technique would be an effective treatment for MHRD.…”
Section: Introductionmentioning
confidence: 93%
“…Kuriyama and Michalewska et al 21, 22 also found that the inverted ILM flap technique contributed to a high macular hole closure rate in highly myopic eyes. We therefore hypothesized that the inverted ILM flap technique would be an effective treatment for MHRD.…”
Section: Introductionmentioning
confidence: 93%
“…10 Thus, the posturing position and the duration of the postoperative prone position were different among institutions. Certainly, eliminating the need for a prone position or long-acting gas tamponade would be better for patients.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there were reports showing the efficacy of this technique for surgical repair of macular holes in high myopia. 9,10 However, detailed anatomical changes in the process of hole closure in eyes with retinal detachment have not yet been reported. In this study, we report on three cases of MHRD in high myopia in which macular holes were successfully closed over residual subretinal fluid with the inverted ILM bridging the holes.…”
mentioning
confidence: 98%
“…They documented 100% closure of MH at the first week proved by OCT with improved mean snellen visual acuity from 0.09 to 0.41. 19 …”
Section: Discussionmentioning
confidence: 99%
“…SD-OCT images confirmed that the process of foveal architectural repair after this surgery continues over at least a 12-month period. 19 …”
Section: Introductionmentioning
confidence: 99%